Gambaran Faktor Risiko Intauterine Fetal Death di RSUD Abdul Wahab Sjahranie Samarinda Periode 2017-2018 - Nursaci Mardania (ITKES Wiyata Husada Samarinda, 2019)
ABSTRACT Intrauterine Fetal Death (IUFD) is fetal death after 20 weeks gestation, classified as early IUFD, if it occurs before 24 weeks gestation, and advanced IUFD, if it occurs after 24 weeks of gestation. This study aimed to determine the description of risk factors for IUFD in Abdul Wahab Sjahranie Hospital Period 2017 - 2018. The method used descriptive observational with cross sectional design. Samples were pregnant women diagnosed with IUFD at Abdul Wahab Sjahranie Hospital Samarinda in 2017 - 2018. Data analyse used univariate analysis. The results showed that preterm gestational age was 72,8%, aterm 27,2%, postterm 0%; maternal age <20 years 11,1%, 20 - 35 years 63%,> 35 years 25,9%; nulliparous parity 32,1%, primipara 24,7%, multipara 43,2%; Normal Body Mass Index 46,9%, overweight 30,9%, obesity 22,2%; gestational hypertension 1,2%, chronic hypertension 0%, preeclampsia 17,3%, eclampsia 0%, anemia 27,2%, diabetes mellitus 6,3%, non-diseased mothers 48,1%; mothers with amusement 1,2%, who are not amused 98,8%; umbilical prolapse abnormalities of 1,2%, umbilical cord twist 0%, and do not have umbilical cord abnormalities 98,8%; placental abruption 4,9%, and no placental abruption 95,1%. It was concluded that the frequency of IUFD was most common in preterm mothers, ages 20-35 years, multiparous, normal BMI, mothers who were not diseased, not amused, had no umbilical prolapse, and had no placental abruption. Keyword : Pregnant Women, IUFD, Risk Factors